Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T11:11:20+01:00
X *(x-2) = 3

x² - 2x = 3

x² - 2x - 3 = 0

Δ=4-4*1*(-3) = 16

x1 = 2-4 /2 = -1
x2 = 2+4 /2 = 3

to będzie para liczb:
-1 i -3
lub
3 i 1
2010-02-07T11:11:40+01:00
Iloczyn, nie iloraz.. grr

x * (x - 2) = 3
x² - 2x = 3
x² - 2x - 3 = 0
Δ = 4 - [4*1*(-3)] = 16
Δ = 4 - [-12]
Δ = 4+12
Δ = 16
√Δ = 4

x₁ = 2-4/2 = -1
x₂ = 2+4/2 = 3

x = 3 lub x = -1
2010-02-07T11:18:08+01:00
X, x-2 -szukane liczby
x*(x-2)=3
x²-2x=3
x²-2x-3=0
Δ=4-4*(-3) = 16
√Δ=4

x1 = (2-4)/2 = -1 lub x2 =(2+4)/2 = 3
x1-2=-3 x2-2=1

Odp: Rozwiązaniem jest para liczb -1 i -3 lub 3 i 1.